CLOUD COMPUTING TECHNOLOGIES FOR GREEN ENTERPRISES - LIEPONIENĖ, Jurgita (Taikomieji tyrimai studijose ir praktikoje - Applied research in studies and practice, 2022)
Nowadays, enterprises are encouraged to develop greener solutions. Regulations is getting stronger and stronger regarding the reduction of emissions, energy, water consumption or waste. Information technology plays a vital role in every business. Enterprises use information technologies to run their operations, manage their data, collaborate, communicate, and make decisions. Cloud computing technologies could help companies adopt much greener business practices. This paper examines how cloud computing technologies could help enterprises to become greener, analyses the use of cloud computing services by enterprises, analyses the implementations of green IT attributes in the cloud computing.